Teaching and learning clinical skills and medical competences - Kira, Célia Maria; Martins, Milton de Arruda (Medicina (Ribeirao Preto), 1996)
Undergraduate medical educations have to cover not only cognitive aspects but also skills and attitudes. In order to fulfill this objective, new trends have been incorporated into teaching, including training in outpatient clinics, notions of cost-efficiency analysis in clinical decision-making, multiprofessional team approach, the physicians role in health maintenance and prevention of disease, notions of clinical epidemiology and an increased value on psychosocial and cultural aspects related to diseases and patient’s life. There are a number of ways to teach clinical reasoning, including a combination of thought and pattern recognition. These strategies have been taken into consideration to the introduction of changes in the teaching of basic clinical skills at the University of São Paulo Faculty of Medicine, which are briefly described in this paper. The authors also comment on the importance of some current recommendations, such as early student exposition to real patients, small group teaching, problem-based learning and self-learning skills and the practice of evidence-based Medicine. It is particularly stressed the role of medical teachers, who must be competent physicians, efficient supervisors, learning facilitators as well as suitable role models regarding positive attitudes towards the patient, his/her family and colleagues and other members of the health team.